2011
DOI: 10.1097/mbc.0b013e3283444ddb
|View full text |Cite
|
Sign up to set email alerts
|

Severe prekallikrein deficiency due to a homozygous Trp499Stop nonsense mutation

Abstract: Prekallikrein deficiency is a rare autosomal recessive disease not considered to be associated with a tendency for bleeding, despite marked prolongation of activated partial thromboplastin time. Currently, six kinds of mutations in the prekallikrein gene are known to be associated with prekallikrein deficiency. In this report, we describe a patient with idiopathic thrombocytopenic purpura who was recognized to have severe prekallikrein deficiency. Molecular analysis of the patient's prekallikrein gene showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 12 families with a total of 20 patients were gathered [8][9][10][11][12][13][14][15][16][17][18]. The main features of these families are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 families with a total of 20 patients were gathered [8][9][10][11][12][13][14][15][16][17][18]. The main features of these families are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal localization of the gene has been mapped to the q34-q35 region on the long arm of chromosome 4, encoded by a single gene ( KLKB1 ), and composed of 15 exons and 14 introns [8]. Seven types of mutations in prekallikrein deficient families have been identified by molecular genetic analysis, with most mutations being found in the light chain region of the prekallikrein gene [9]. …”
Section: Discussionmentioning
confidence: 99%
“…In 1973, Wuepper et al showed that the "Fletcher factor" was actually PK [4]. It is an autosomal recessive disorder with more than seven different types of mutation identified by molecular genetic analysis [5]. PK deficiency has been classified as type I and type II based on the level of activity and antigen.…”
Section: Discussionmentioning
confidence: 99%